2019
DOI: 10.1002/cphc.201900844
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of AIB1 in Breast Cancer Cells Based on Aptamer‐Functionalized Nanomotors

Abstract: Herein, we report ultrasound‐propelled graphene‐oxide coated gold nanowire motors, functionalized with fluorescein‐labeled DNA aptamers (FAM‐AIB1‐apt), for qualitative detection of overexpressed AIB1 oncoproteins in MCF‐7 breast cancer cells. The movement of nanomotors under the ultrasound field facilitated intracellular uptake and resulted in a faster aptamer binding with the target protein and thus faster fluorescence recovery. The propulsion behavior of the aptamer functionalized nanomotors greatly enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…A similar approach of intracellular sensing was reported for the detection of E6 miRNA in the human papilloma virus associated with oropharyngeal cancer [230]. Subsequently, Beltrán-Gastélum et al [17] also reported a similar sensing strategy for qualitative detection of cancer biomarker, known as amplified in breast cancer (AIB1), and frequently overexpressed in breast cancer (Figure 15). GO modified AuNWs were functionalized with fluorescein labeled aptamer specific to AIB1 (FAM-AIB1-apt) and propelled towards MCF7 cells.…”
Section: Nanomotors Modified By Aptamersmentioning
confidence: 74%
See 1 more Smart Citation
“…A similar approach of intracellular sensing was reported for the detection of E6 miRNA in the human papilloma virus associated with oropharyngeal cancer [230]. Subsequently, Beltrán-Gastélum et al [17] also reported a similar sensing strategy for qualitative detection of cancer biomarker, known as amplified in breast cancer (AIB1), and frequently overexpressed in breast cancer (Figure 15). GO modified AuNWs were functionalized with fluorescein labeled aptamer specific to AIB1 (FAM-AIB1-apt) and propelled towards MCF7 cells.…”
Section: Nanomotors Modified By Aptamersmentioning
confidence: 74%
“…Interaction of aptamer with cancer markers caused its folding, moving the fluorescent probe away from the GO. This is accompanied by increase of fluorescence [17].…”
Section: Introductionmentioning
confidence: 89%
“…Besides the conventional methods such as IHC and fluorescent in situ hybridization (FISH), the new techniques will be developed to measure the expression and amplification of the SRC-3 gene. A recent study invented a new method for monitoring SRC-3 levels in a breast cancer cell based on aptamer-functionalized nanomotors [ 174 ]. However, whether this method can be used to detect SRC-3 in tissues needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fluorescein-labeled aptamers conjugated with an ultrasound-propelled gold nanowire motors (FAM-AIB1-apt) coated with graphene-oxide (C 140 H 42 O 20 ) was used for qualitative diagnosis of overexpressed AIB1 oncoproteins in breast cancer cells (MCF-7). The nanomotor movement in the ultrasound field ensured the faster uptake and binding of the aptamers with the target and results in fluorescence [ 50 ]. The propulsion of the nanomotors conjugated with aptamer significantly increased the fluorescence intensity, in comparison to the static conditions.…”
Section: Aptamers In Cancer Diagnosismentioning
confidence: 99%